The Benjamin-Bona-Mahony equation on modulation spaces - Banquet Brango, Carlos (2021)
In this work we derive time-decay and Strichartz estimates for the generalized Benjamin-Bona-Mahony equation on the framework of modulation spaces Msp,q. We use this results to analyze the existence of local and global solutions of the corresponding Cauchy problem with rough data in modulation spaces. The results improve known results in Sobolev spaces in some sense.